Diagnostic performance of digital breast tomosynthesis with a wide scan angle compared to full-field digital mammography for the detection and characterization of microcalcifications. Issue 12 (December 2016) - Clauser, Paola; Nagl, Georg; Helbich, Thomas H.; Pinker-Domenig, Katja; Weber, Michael; Kapetas, Panagiotis; Bernathova, Maria; Baltzer, Pascal A.T.
Highlights: Wide scan-angle DBT alone shows a high detection rate for microcalcifications. DBT and FFDM can characterize microcalcifications at a comparable level. Characterization is influenced by reader and by lesion type (benign vs malignant). DBT might be used as a stand-alone technique for the assessment of microcalcifications. Abstract: Objectives: To assess the diagnostic performance of digital breast tomosynthesis (DBT), with a wide scan-angle, compared to full-field digital mammography (FFDM), for the detection and characterization of microcalcifications. Methods: IRB approval was obtained for this retrospective study. We selected 150 FFDM and DBT (50 benign and 50 malignant histologically verified microcalcifications, 50 cases classified as BI-RADS 1). Four radiologists evaluated, in separate sessions and blinded to patients' history and histology, the presence of microcalcifications. Cases with microcalcifications were assessed for visibility, characteristics, and grade of suspicion using BI-RADS categories. Detection rate and diagnostic performance were calculated. Visibility, lesions' characteristics and reading time were analysed. Results: Detection rate and visibility were good for both FFDM and DBT, without intra-reader differences (P = 0.510). Inter-reader differences were detected (P < 0.018). Only two lesions were not detected by any reader on either FFDM or DBT. Diagnostic performance with DBT was as good as that of FFDM, but a significant inter-reader difference was found (P = 0.041). High inter-reader variability in the use of the descriptors was found. Reading time for DBT was almost twice that for FFDM (44 and 25 s, respectively). Conclusion: Wide scan-angle DBT enabled the detection and characterization of microcalcifications with no significant differences from FFDM. Inter-reader variability was seen.